The Value System In Quranic Discourse And The Establishment Of Human Commonality (An Analytical Study Of Methodological Foundations And Maqasidic Dimensions( (Journal of Namibian Studies : History Politics Culture, 2023)
This research provides an in-depth analysis of the value system in Quranic discourse and its role in establishing human commonality. It focuses on examining the methodological foundations and maqasidic dimensions offered by the Quran in constructing a shared value framework among humans. Using analytical and inductive methodologies, the study aims to uncover the Quranic approach to establishing shared human values, with a thorough analysis of the methodological foundations within Quranic discourse for building this value system. The research also seeks to extract the maqasidic dimensions in grounding human commonality, presenting a contemporary vision for addressing human issues from a Quranic perspective. This contributes to providing a comprehensive methodological framework for understanding and activating the Quranic value system in the modern context.